FOOD AND FEEDING HABITS OF OTOLITHES RUBER (SCHNEIDER) AT CALICUT - Nair, K V Somasekharan (Indian Journal of Fisheries, 2011)
The food and feeding habits of Otolitlies ruber from the inshore fishinggrounds off Calicut were studied. No regular periodicity in feeding was observed.The young ones feed mainly at the surface on Acetes and mysiids, while the adultfish feeds at the bottom chiefly on prawns and teleo&ts. The variations in the foodcomposition rre discussed in relation to diff'erent size groups, seasons and environmentalbiota.